2012
DOI: 10.1038/srep00993
|View full text |Cite
|
Sign up to set email alerts
|

A singular thermodynamically consistent temperature at the origin of the anomalous behavior of liquid water

Abstract: The density maximum of water dominates the thermodynamics of the system under ambient conditions, is strongly P-dependent, and disappears at a crossover pressure Pcross ~ 1.8 kbar. We study this variable across a wide area of the T–P phase diagram. We consider old and new data of both the isothermal compressibility KT(T, P) and the coefficient of thermal expansion αP(T, P). We observe that KT(T) shows a minimum at T* ~ 315±5 K for all the studied pressures. We find the behavior of αP to also be surprising: all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 34 publications
4
79
0
1
Order By: Relevance
“…T * is the compressibility minimum temperature of bulk water. It is invariant with increasing pressure, and coincides with the cross-over point at which thermal expansion is found to be constant with pressure (32). T * also signals the breakdown of the tetrahedral structure of water (33) and the limit of the protein native state (34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T * is the compressibility minimum temperature of bulk water. It is invariant with increasing pressure, and coincides with the cross-over point at which thermal expansion is found to be constant with pressure (32). T * also signals the breakdown of the tetrahedral structure of water (33) and the limit of the protein native state (34).…”
Section: Resultsmentioning
confidence: 99%
“…In normal liquids δS and δV fluctuations become smaller as T decreases and they are positively correlated, but in water they become more pronounced at T * and are anticorrelated at the density maximum (at ambient pressure). Structurally T * is identified as the onset temperature of HB clustering (32). Such transport properties as self-diffusion data in the high-temperature regime of bulk water D s ðTÞ indicate that T * signals a new dynamic cross-over.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mallamace et al also noted that the minimum in K T is nearly pindependent, and occurs at a temperature T * = 0.49 T c , coinciding almost exactly with the central vertical line of our narrow slab. Mallamace et al identified as well some other special features of T * and concluded that the "singular and universal expansivity point" [31] at T * , and the crossover pressure p cross , characterize the thermodynamic and structural properties of water. In addition, they suggested that T * may mark the onset of HB clustering with ice-like low-density liquid (LDL) structures more compressible than the high-density liquid (HDL) structures at higher T .…”
Section: (B) For An Expanded View (Argon Is Shown For Comparison Inmentioning
confidence: 99%
“…2(d). In recent studies of experimental data, Mallamace et al [30,31] analyzed the (p, T ) dependence of several thermodynamic response functions to find limits of regions with anomalous behavior. These authors reported that the isobaric density maximum is strongly p-dependent, and that it disappears above a certain crossover pressure p cross ∼ 8.1p c , coinciding closely with the top of our positive R narrow slab region in Fig.…”
Section: (B) For An Expanded View (Argon Is Shown For Comparison Inmentioning
confidence: 99%